2017
DOI: 10.1097/iop.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Neurofibroma/Schwannoma of the Supraorbital Nerve: Clinicopathologic Correlation of a Rare Tumor

Abstract: Benign peripheral nerve sheath tumors such as schwannoma and neurofibroma have long been considered distinct entities. Recently, hybrid tumors demonstrating combined morphological features of neurofibroma and schwannoma have been described, primarily in dermal locations. Only 1 case of hybrid peripheral nerve sheath tumor of the orbit has been reported in the literature. Hybrid morphology is important to recognize because of its association with the neurofibromatoses, including schwannomatosis; however, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Malignant transformation and recurrence were reported in cases of extra-orbital neurofibroma-perineurioma hybrid. 1,2 Our index patient remained symptom-free without recurrence at 6 months. Long-term follow-up and study into pathogenesis of HPNST are required for this rare but important tumour.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…Malignant transformation and recurrence were reported in cases of extra-orbital neurofibroma-perineurioma hybrid. 1,2 Our index patient remained symptom-free without recurrence at 6 months. Long-term follow-up and study into pathogenesis of HPNST are required for this rare but important tumour.…”
mentioning
confidence: 66%
“…5,6 Literature review identified only 2 cases of orbital HPNST, both of neurofibroma-schwannoma subtype. 2,3 We report the third case of orbital HPNST in the distribution of supratrochlear nerve that extended toward the orbital apex, evidenced by loss of sensory innervation after excision. It is also the first reported neurofibroma-perineurioma subtype to occur within the orbit.…”
mentioning
confidence: 93%
See 3 more Smart Citations